The Recognition of the Nonclassical Major Histocompatibility Complex (MHC) Class I Molecule, T10, by the γδ T Cell, G8 - Crowley, Michael P. (The Rockefeller University Press, 1997)
Recent studies have shown that many nonclassical major histocompatibility complex (MHC) (class Ib) molecules have distinct antigen-binding capabilities, including the binding of nonpeptide moieties and the binding of peptides that are different from those bound to classical MHC molecules. Here, we show that one of the H-2T region–encoded molecules, T10, when produced in Escherichia coli, can be folded in vitro with β(2)-microglobulin (β(2)m) to form a stable heterodimer in the absence of peptide or nonpeptide moieties. This heterodimer can be recognized by specific antibodies and is stimulatory to the γδ T cell clone, G8. Circular dichroism analysis indicates that T10/β(2)m has structural features distinct from those of classical MHC class I molecules. These results suggest a new way for MHC-like molecules to adopt a peptide-free structure and to function in the immune system.